Sirtuin Type 1 Mediates the Antidepressant Effect of S-Ketamine in a Chronic Unpredictable Stress Model - Hou, Lanwei; Miao, Jingyu; Meng, Haiwei; Liu, Xiao; Wang, Di; Tan, Yawen; Li, Chuangang (Frontiers in Psychiatry, 2022)
Background: Major depressive disorder (MDD) refers to a mental disease with complex pathogenesis and treatment mechanism. S-ketamine exhibited high effectiveness in treating MDD. However, the pharmacological activity of S-ketamine has not been reported yet. Materials and Methods: In this study, depression-like characteristics were induced by chronic unpredictable stress (CUS). After S-ketamine (15 mg/kg) was intraperitoneally injected, the behaviors of mice were tested by conducting open-field test, elevated plus maze test, tail suspension test, and forced swimming test. Bilateral injection of sirtuin type 1 (SIRT1) inhibitor EX-527 was injected into the medial prefrontal cortex (mPFC) to upregulate the SIRT1 expression. The expression of SIRT1 and brain-derived neurotrophic factor (BDNF) was detected by conducting Western blot and immunofluorescence assays. Meanwhile, the synaptic ultrastructure was detected by transmission electron microscopy. Results: In this study, the mice showed depression-like behavior in a series of behavioral tests. After the treatment with S-ketamine, the depression-like behavior stopped. Further, the synaptic ultrastructure in mPFC, including the decreased curvature of the post synaptic density and thinning of the postsynaptic density, improved after the S-ketamine treatment. Moreover, we found that S-ketamine had the possibility of spontaneous binding with SIRT1 at the molecular level and reversed CUS-induced SIRT1 reduction. Meanwhile, a positive relationship between SIRT1 and BDNF expression in mPFC and SIRT1 inhibitor limited the role of S-ketamine in reducing the depression-like behavior and increasing the BDNF level. Conclusion: S-ketamine upregulated the SIRT1-mediated BDNF in mPFC and reversed the synaptic structural defects caused by CUS. SIRT1 is a mediator of S-ketamine in alleviating depression-like behavior.